Pro-phagocytic function and structural basis of GPR84 signaling - Xuan Zhang; Yujing Wang; Shreyas Supekar; Xu Cao; Jingkai Zhou; Jessica Dang; Siqi Chen; Laura Jenkins; Sara Marsango; Xiu Li; Guibing Liu; Graeme Milligan; et al. (Nature Communications, 2023)
Abstract GPR84 is a unique orphan G protein-coupled receptor (GPCR) that can be activated by endogenous medium-chain fatty acids (MCFAs). The signaling of GPR84 is largely pro-inflammatory, which can augment inflammatory response, and GPR84 also functions as a pro-phagocytic receptor to enhance phagocytic activities of macrophages. In this study, we show that the activation of GPR84 by the synthetic agonist 6-OAU can synergize with the blockade of CD47 on cancer cells to induce phagocytosis of cancer cells by macrophages. We also determine a high-resolution structure of the GPR84-Gi signaling complex with 6-OAU. This structure reveals an occluded binding pocket for 6-OAU, the molecular basis of receptor activation involving non-conserved structural motifs of GPR84, and an unusual Gi-coupling interface. Together with computational docking and simulations studies, this structure also suggests a mechanism for the high selectivity of GPR84 for MCFAs and a potential routes of ligand binding and dissociation. These results provide a framework for understanding GPR84 signaling and developing new drugs targeting GPR84.